Six Trees: Thinking along a Spectrum to Escape a Dark Wood - Katz, Eric (Environmental ethics, 2023)
Consider the existence of six identical trees of the same species across a variety of environments. The first tree is in a wild and isolated landscape. The second is in a wilderness park. The third is in a heavily forested "tree plantation" owned by International Paper. The fourth is in the Ramble in Central Park. The fifth is in a suburban yard. The sixth is inside the six-story atrium of a Manhattan skyscraper. This paper begins with the intuition that the identical trees have different values because they exist in different environments and biological-social contexts. To understand the different evaluations of the trees we must think along a spectrum that incorporates both axiology and ontology. This thought experiment is useful in exploring arguments about both the management and the preservation of the natural world. The conclusion is that we must think along a spectrum of natural being and value to understand the dualism between humanity and nature and thereby avoid the domination of the natural environment.